Strengthening the Competitiveness of MSME Products Through Legal Certification, Socialization Strategies, and Assistance - Arfa, Daghastaniy Fairuzza; Rofiqoh, Yusnia I'anatur; Sharf, Oely Maqwa; Ashar, Sofia; Rochmah, Zuwaroh Kholifatur; Ningrum, Cherly Fitria (Universitas Muhammadiyah Sidoarjo, 2024)
Business legality is a fundamental aspect in strengthening the identity and competitiveness of MSME players, especially in facing market competition and increasingly selective consumer demands. This community service activity aims to provide understanding and direct guidance to SMEs in Baureno Sub-district, Bojonegoro Regency, regarding the importance of business and product legality, particularly in obtaining an NIB (Business Identification Number), PIRT (Home Industry Product Registration), and halal certification. The activity was conducted in the form of socialization and interactive discussions with a practical approach. The results of the activity showed an increase in participants' understanding of the importance of business legality and the process of obtaining it. Thus, such guidance is highly relevant for strengthening the administrative and strategic position of SMEs in the digital economy era.